A pilot study of a new app based on self-compassion for the prevention and promotion of mental health among Brazilian college students - Schaab, Bruno Luis; Cunha, Lara Finkler; Silveira, Desiree Cordoni; da Silva, Pamela Carvalho; Ballejos, Kellen Greff; Diaz, Gabriela Bertoletti; Kaiser, Vanessa; Calvetti, Prisla Ücker; Cazella, Sílvio César; Barros, Helena Maria Tannhauser; Reppold, Caroline Tozzi (Frontiers in Psychology, 2024)
Introduction: Epidemiological data suggest substantial issues on the mental health of university students worldwide. Self-compassion is associated with lower rates of psychological distress and better positive mental health. Thus, we have developed a app-based intervention based on selfcompassion principles targeting the prevention and promotion of mental health in college students. The current pilot study assessed adherence to intervention, preliminary mental health benefits, and satisfaction and acceptability with the app among Brazilian college students.The study employed a pre-experimental single-group design along with pre-test and posttest assessments (n = 23). A mixed methods approach was utilized to comprehensively assess the outcomes of the intervention.The overall adherence rate for the intervention was 37.87%, with 26.26% of participants successfully completing all modules. Among the 21 outcomes assessed, 15 exhibited statistically significant results. Notably, there was a substantial increase in self-compassion, demonstrating a large effect size (d = 1.15), and a moderate effect size reduction in stress (d = .62) and anxiety (d = .52). All satisfaction indicators for the intervention received scores above 7. The intervention was well-received by participants who completed it, although a potential barrier identified was the volume of text within the app and the need to adopt a more playful and concise format for the intervention. Discussion: Despite a notable participant dropout, the adherence to intervention aligns with patterns observed in other online interventions conducted in real-world settings. The observed mental health benefits, high satisfaction levels, and positive acceptance underscore the rationale for pursuing a subsequent randomized clinical trial.